ANALISIS IN SILICO GENISTEIN DAN ANALOGNYA SEBAGAI INHIBITOR KANKER PAYUDARA RESEPTOR ESTROGEN ALFA POSITIF (ERÎ±+) - Fauzan Zein M (JURNAL FARMASI GALENIKA, 2015)
Breast cancer is the highest mortality disease on women in the world and about 60-80% of the cases are ERÎ±+ breast cancer. The discovery of more selective to HERÎ±, safe, and potential new anticancer agent is expected to help the treatment of ERÎ±+ breast cancer. In silico analysis had been carried out by computational chemistry methods, including determination of physicochemical parameters such as lipophilicity/CLogP, molar refractivity/CMR, bond energy/HOMO-LUMO and E-Gap, partial charge reactivity; determination of structural similarity by overlaying, and the interaction analysis of genistein and its analogues against HERÎ± by docking method. The result showed that group of -7OH on the C ring and group of -4'OH on the A ring of genistein were the major pharmacophore. More number of hydrogen bonds (especially to Arg394), shorter distance, and lower free binding energy resulted higher inhibitory activity, it was shown by MA6 which had 4 of hydrogen bonds (14,51 kcal/mol) and each of them bound to Arg394 (=N- aromatic, substituent of -4'OR), Arg394 (-4'OR), His524 (-7OR), and Leu391 (=N- aromatic, substituent of -4'OR). Genistein, MA6, and MA8 had similar activity to tamoxifen even predicted more potent (MA6), it was correlated to its binding with Arg394. The complete result of in silico analysis confirmed the activity of genistein and its analogues as an inhibitor of ERÎ±+ breast cancer.